Bangkitnya Industri Pernikahan Pasca Pandemi Covid 19 dan Dampaknya Bagi Ekonomi Nasional - Fadli Ilyas (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research was conducted to find out how much the Indonesian wedding industry has been impacted by the Covid-19 pandemic that has hit Indonesia recently. The Indonesian wedding industry is slowly but surely recovering, meaning that the growth of the country's wedding industry has increased. One of the factors indicating an increase in this industry is the factor of Indonesia's population growth which has increased. Various strategies were announced, policies were implemented, outreach was carried out until the slogan was echoed so that Indonesia could recover faster and rise stronger. Another effort that is no less made is the many activities of Indonesian wedding exhibitions with various concepts held periodically throughout the year. Starting from the concept of traditional marriage, national to international. For this reason, it is hoped that all parties and elements of society can work together well so that it can run optimally so that the recovery of various aspects, especially the economic aspects that must be restored immediately and the national economy revives. The rise of the Indonesian wedding industry will be reviewed in a SWOT analysis to provide an overview of the increase in the Indonesian wedding industry and its impact on the national economy.